A study of the plateau array : thesis concerning subsection (e), 608 of the Animal Husbandry Section of the Master of Agricultural Science Degree and incorporating work carried out during the tenure of the Farmers' Union Research Scholarship and the Shell Scholarship1938 - Sutherland, J. A. (James Alan) (Massey University, 1939)
A brief historical survey of the work leading up to the present study. The world sheep population is in the vicinity of seven hundred millions and the vast majority of these animals are kept, to a greater or a lesser degree, for their wool. It is, therefore, not surprising that Wool Research is by no means new. The production of sheep for their coat has been, as Barker points out ( 1), of importance since Biblical times and, although during the last epoch, with the perfection of methods for meat preservation, the importance of wool to the sheep industry has decreased, the need for wool research has been increased by the ever growing perfection of synthetic fibres. Wool research as such can possibly be dated from Dr. Hook who, in 1664, presented a paper to the Royal Society on the subject of wool and hair structure, but it was not until the advent of the compound microscope that the study of wool gained sufficient precision for measurements to be made. Such measurements opened the door for the wool physicist who, by the application of x-rays and other physical methods, has been able to explore with considerable success the ultimate structure of wool and hair. The value of wool has been determined, at least partially, by its length and thickness (or width), and thus measurements of wool in three dimensions have been important sections of wool research. As other valuable characters were recognised and evaluated they also were measured and correlations worked out. Thus it has come about that wool research has collected about itself innumerable patient measurements - measurements that have often merely evidenced the complexity of the fleece of the sheep as a subject of research.
Keywords: Wool; Romney marsh sheep